Preparation of Innovative PEG/Tannic Acid/TiO2 Hydrogels and Effect of Tannic Acid Concentration on Their Hydrophilicity - Turk, Serbülent; Ünlü, Burak; Mustapa, Mohammad Sukri (International Journal of Integrated Engineering, 2021)
Hydrogels are materials that can be used in biomedical and medical applications and have gained increasing interest in recent years. In order to obtain a wide variety of properties, hydrogels containing more innovative components still need to be produced and investigated. In this study, for this purpose, an innovative injectable polyethylene glycol (PEG)/tannic acid (TA)/TiO2 hydrogels were prepared and their properties were investigated. TA, used as a crosslinker for PEG, was used in different concentrations (400 mg, 800 mg, and 1.2 g) in hydrogel preparation to analyse the effect of tannic acid on the properties of the obtained hydrogels. PEG/0.4TA/TiO2, PEG/0.8TA/TiO2 and PEG/1.2TA/TiO2 hydrogels prepared by using FeCl3 to increase the crosslink density in its content and by adding TiO2 due to its antimicrobial properties, were characterized by UV-VIS spectroscopy, FTIR and contact angle measurements. . With the UV-VIS and FTIR spectra, it is seen that TA/Fe3+ metal complexes are formed and the three-dimensional hydrogel network is successfully completed with the help of these metal complexes formed by the addition of FeCl3. In addition, the contact angle measurements of the PEG/0.4TA/TiO2, PEG/0.8TA/TiO2 and PEG/1.2TA/TiO2 hydrogels were found to be 18°, 27° and 27° degrees, respectively, and the hydrophilicity of the hydrogels was reached at constant value in the samples added 0.8 g TA. The obtained new injectable PEG/TA/TiO2 hydrogel is promising for use in biomedical and medical fields, thanks to its contact angle values ​​of less than 90° for biocompatibility and its biocompatible components.